(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Cryogenic electron microscopy (cryo-EM) has revolutionized structural biology by enabling high-resolution determination of biomolecular structures without the need for crystallization. Technological advancements in electron optics, direct electron detectors, image processing algorithms, and specimen preparation have driven a “resolution revolution” in cryo-EM, pushing achievable resolutions into the near-atomic and atomic regimes. Innovations now allow visualization of side chains, individual atoms, and in exceptional cases even hydrogen atoms, dramatically expanding cryo-EM’s utility in fundamental research and structure-based drug design. This article reviews the principles, methodologies, applications, breakthroughs, limitations, and future directions of cryo-EM in solving atomic-level biomolecular structures. It highlights recent achievements and discusses how integration with computational tools and AI methods is further enhancing structural determination and interpretation.